2020
DOI: 10.1038/s41557-020-0429-0
|View full text |Cite
|
Sign up to set email alerts
|

Odd–even alternations in helical propensity of a homologous series of hydrocarbons

Abstract: Odd and even homologues of some n-alkane-based systems are known to exhibit significantly different trends in solid state properties; a well-known illustration is the zigzag plot of their melting point versus chain length. Odd-even effects in the solid state often arise from intermolecular interactions involving fully extended molecules. These effects have also been observed in less condensed phases, such as self-assembled monolayers; however, the origins of these effects in such systems can be difficult to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…93 However, this explanation does not apply to isolated polymer chains, which do not exhibit any crystalline aggregates. An alternative mechanism, which has been demonstrated for alkyl chains in solution, links the odd/effect to alkyl chain conformations and their population, 94,95 in alignment with our observations that isolated odd and even CBS-m polymer chains have different sizes of the conformational space they can populate.…”
Section: Isolated Chain Dynamicssupporting
confidence: 88%
“…93 However, this explanation does not apply to isolated polymer chains, which do not exhibit any crystalline aggregates. An alternative mechanism, which has been demonstrated for alkyl chains in solution, links the odd/effect to alkyl chain conformations and their population, 94,95 in alignment with our observations that isolated odd and even CBS-m polymer chains have different sizes of the conformational space they can populate.…”
Section: Isolated Chain Dynamicssupporting
confidence: 88%
“…Parity effects in solid condensed phases often arise from differences in the intermolecular interactions and molecular packing. A classic example is the odd–even variation of the melting points of solids of odd- and even-numbered n -alkanes and n -alkyl carboxylic acids. , SAM properties exhibiting parity effects include surface wettability, friction, and electron transfer rate . Charge tunneling across metal–SAM–metal junctions is particularly sensitive to the SAM structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the odd−even sidechain length of n-alkyl-substituted homologues significantly affects their packing configuration and consequently alters the water affinity. 33,34 We speculate that a similar odd−even effect might account for the water content changes along with Cn in our Cn-0.5 series. Explicit explanation of such a relationship between water content and odd−even alkyl chain length is a complex task and remains an interesting subject for future exploration.…”
Section: Resultsmentioning
confidence: 65%